Application Exploration of Virtual Network Technology in Computer Network Security - Zhou, Weiwei (Journal of Artificial Intelligence and Information, 2025)
To safeguard the security of computer network information systems and effectively address network information risks, such as Trojan viruses and hacker intrusions, it is crucial to actively employ advanced technologies. This article takes virtual network technology as its subject of study and provides a brief overview of virtual network technology and the significance of computer network security. It delves into its applications in computer network security from four aspects: technology types, application scope, real-world impact, and effective measures. The aim is to reinforce the stability of computer networks and protect user information security, providing valuable insights for relevant individuals.